(untitled) (Research, Society and Development, 2021)
This research is of a qualitative nature, of a bibliographic nature, with a focus on the practice of research in the history of education, according to the guidelines suggested by Luca (2020). The starting point is a clash that occurred in the course of the Ceará school reform, in the beginning of the 1920s, involving the educator Lourenço Filho (1897-1970 and Father Cícero Romão (1844-1934). responds to the School Register The development of this study was done in two stages: in the first, the analytical reading of the work Juazeiro do Padre Cícero (2002), authored by the aforementioned educator from São Paulo, was made, taking as a point of analysis a comment contained on page 12 of the preface made by researcher Carlos Monarcha, from UNESP, about the priest’s resistance, hampering the progress of Ceará’s reform. , beginning the second stage. The crossing of such readings, allowed a mapping and an outline of the historical territory where that ideological duel was fought, in a cultural context totic: urban versus rural. It is admitted that the expansion of the understanding of this issue, in the light of the set of the appropriate readings, is opportune to reflect the project of reform of the primary education, whose public school should have been offered to the masses, in that historical scenario of the Ceará education, above the ideological and religious interests and beliefs.